PENGARUH LITERASI KEUANGAN SYARIAH, HALAL LIFESTYLE DAN RELIGIUSITAS TERHADAP MINAT TALANGAN UMROH DI BANK SUMUT SYARIAH - Dwi Purnama Sari; Muhammad Irwan Padli Nasution; Andri Soemitra (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the influence of Islamic financial literacy, halal lifestyle, and religiosity on the interest in using Umrah advances among Bank Sumut Syariah customers. The increasing need of the Muslim community to perform the Umrah pilgrimage encourages the importance of providing financing in accordance with Sharia principles. The study used a quantitative approach with a survey method. The study population was 130 customers using the Umrah advance facility of Bank Sumut Syariah as of April 2026. A sample of 98 respondents was determined using the Slovin formula with a 5% error rate. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results showed that Islamic financial literacy had a positive and significant effect on the interest in Umrah advances (sig. 0.000). Halal lifestyle also had a positive and significant effect (sig. 0.001), while religiosity had a positive and significant effect (sig. 0.000) and was the most dominant variable. Simultaneously, all three variables had a positive and significant effect on the interest in Umrah advances (sig. 0.000). The coefficient of determination (R²) of 0.615 indicates that 61.5% of the variation in interest in Umrah financing can be explained by these three variables. This finding underscores the importance of knowledge, a halal lifestyle, and religiosity in increasing public interest in Sharia-based pilgrimage financing.